Evaluating domestication and ploidy effects on the assembly of the wheat bacterial microbiome. - Heidi M L Wipf; Devin Coleman-Derr (PLoS ONE)
While numerous studies implicate the microbiome in host fitness, contributions of host evolution to microbial recruitment remain largely uncharacterized. Past work has shown that plant polyploidy and domestication can influence plant biotic and abiotic interactions, yet impacts on broader microbiome assembly are still unknown for many crop species. In this study, we utilized three approaches-two field studies and one greenhouse-based experiment-to determine the degree to which patterns in bacterial community assembly in wheat (Triticum sp.) roots and rhizospheres are attributable to the host factors of ploidy level (2n, 4n, 6n) and domestication status (cultivated vs. wild). Profiling belowground bacterial communities with 16S rRNA gene amplicon sequencing, we analyzed patterns in diversity and composition. From our initial analyses of a subsetted dataset, we observed that host ploidy level was statistically significant in explaining variation in alpha and beta diversity for rhizosphere microbiomes, as well as correlated with distinct phylum-level shifts in composition, in the field. Using a reduced complexity field soil inoculum and controlled greenhouse conditions, we found some evidence suggesting that genomic lineage and ploidy level influence root alpha and beta diversity (p-value<0.05). However, in a follow-up field experiment using an expanded set of Triticum genomes that included both wild and domesticated varieties, we did not find a strong signal for either diploid genome lineages, domestication status, or ploidy level in shaping rhizosphere bacterial communities. Taken together, these results suggest that while host ploidy and domestication may have some minor influence on microbial assembly, these impacts are subtle and difficult to assess in belowground compartments for wheat varieties. By improving our understanding of the degree to which host ploidy and cultivation factors shape the plant microbiome, this research informs perspectives on what key driving forces may underlie microbiome structuring, as well as where future efforts may be best directed towards fortifying plant growth by microbial means. The greatest influence of the host on the wheat microbiome appeared to occur in the rhizosphere compartment, and we suggest that future work focuses on this environment to further characterize how host genomic and phenotypic changes influence plant-microbe communications.